LEGAL PROBLEMS REGARDING DISPUTES IN GOVERNMENT PROCUREMENT OF GOODS AND SERVICES IN CORRECTIONS INSTITUTIONS - Bangun, Revanda; Arifin, Muhammad; Nadirah, Ida (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Procurement goods and services government is part important in operate wheel state administration , including in the environment institution correctional . However , in In practice , this process often face various problems law that triggers dispute . Research This discuss reason main dispute procurement goods and services in the institution correctional , such as mismatch procedure with applicable regulations , misuse​ authority , conflict interests , and minimal transparency . In addition , the obstacles in implementation the rules that are set in Presidential Decree No. 16 of 2018 concerning Government Procurement of Goods/Services participate to worsen situation . The dispute that arose often leading to a long legal process and impacting efficiency organization task socialization . Research This recommend existence improvement supervision , transparency , and implementation sanctions firm For minimize dispute in procurement goods and services in the institution correctional